Design strategies and emerging applications for mechanically interlocked molecules - Fredrik Schaufelberger; Serena Silvi; Jose Berna (Communications Chemistry)
Communications Chemistry is pleased to introduce a Collection of articles on the design and applications of mechanically interlocked molecules. Here, the Guest Editors introduce the topic, outline recent advances in the field, and provide their thoughts for future directions of research.